Analisis Ketahanan Pangan Rumah Tangga Petani di Desa Ulee Lhat Kecamatan Montasik Kabupaten Aceh Besar - Elly Susanti; T. Fauzi; Taufiqurrahman Taufiqurrahman (Jurnal Bisnis Tani, 2018)
One way to improve the productivity of smallholder plantations are mainly located in dry land is the cropping pattern of intercropping. Intercropping ensure the success of planting face uncertain climate, pests and disease, as well as price fluctuation. The purpose of this research was to determine differences in the income of farmers and land productivity in defferent cacao intercropping planting patterns on cocoa farms in the district Geulumpang Tiga. Sample in this study is 52 people were taken by Proportioned Statified Random Sampling. The method used is the analysis of profitability and productivity of cocoa plantations. Based on the analysis results obtained that the cropping pattern V has the highest income in the amount of Rp 9.508.511 per hectare per year. While the productivity of cacao plantations are highest in the cropping pattern V in the amount of 427 kg/ha/year.